A voltage coordination control strategy based on the reactive power-active network loss partitioned aggregation domain. (January 2023) - Wang, Zhenhao; Tan, Weixian; Li, He; Ge, Jinming; Wang, Wei
Highlights: A zoning method based on reactive power-voltage sensitivity weights and active network loss-voltage sensitivity weights is proposed. This method is based on the established modularity function model for partitioning. Based on the two weight partitioning results, the concept of aggregation domain is proposed. Voltage control is performed from the aggregation domain results obtained above. Abstract: As the scale of the power system continues to expand, it becomes more difficult to regulate the voltage of large grids in a unified manner by traditional control methods. In this paper, based on the theory of modularity function model in complex networks, a voltage coordination control method of partitioning the aggregated domain of reactive-voltage sensitivity weights and active network loss-voltage sensitivity weights of power systems is proposed. Firstly, the system is partitioned according to the modularity function model and the concept of aggregation domain is proposed. Secondly, the reasonableness of the aggregation domain is judged by using the proposed reactive power support capability index, and the partitioned voltage control strategy is proposed to realize the optimal and reasonable control of the voltage crossing point. Finally, the simulation experiment compares the voltage regulation results of the centralized control method and the zonal control method. The zoned control method provides a relative voltage improvement of 3.27% over the centralized control method, the active network loss of the zoned control method is 3.30% less than that of the centralized control method, and a relative reduction in time of use of 90.70%. The simulation results show that the proposed method can effectively reduce the search range of reactive power compensation devices, reduce the number of nodes for coordinated control, reduce the active network loss of the system due to voltage regulation, and ensure the control capability of reactive power compensation devices within the partition.